Exploring the Applications of the Photoprotective Properties of Anthocyanins in Biological Systems - Hélder Oliveira (International Journal of Molecular Sciences, 2020)
Due to their physical and chemical characteristics, anthocyanins are amongst the most versatile groups of natural compounds. Such unique signature makes these compounds a focus in several different areas of research. Anthocyanins have well been reported as bioactive compounds in a myriad of health disorders such as cardiovascular diseases, cancer, and obesity, among others, due to their anti-inflammatory, antioxidant, anti-diabetic, anti-bacterial, and anti-proliferative capacities. Such a vast number of action mechanisms may be also due to the number of structurally different anthocyanins plus their related derivatives. In this review, we highlight the recent advances on the potential use of anthocyanins in biological systems with particular focus on their photoprotective properties. Topics such as skin aging and eye degenerative diseases, highly influenced by light, and the action of anthocyanins against such damages will be discussed. Photodynamic Therapy and the potential role of anthocyanins as novel photosensitizers will be also a central theme of this review.